Bernstein's reverse dictionary / (by) Theodore M. Bernstein with the collaboration of Jane Wagner. - Bernstein, Theodore Menline (Routledge and Kegan Paul, 1976)
'... lists an array of meanings alphabetically that lead you to words you may have momentarily forgotten ...' - Jacket